Preparation of Cu-doped Cd0.1Zn0.9S solid solution by hydrothermal method and its enhanced activity for hydrogen production under visible light irradiation - Kimi, Melody; Leny, Yuliati; Mustaffa, Shamsuddin (Elsevier, 2012)
A series of Cu-doped Cd0.1Zn0.9S solid solution with various amounts of Cu dopant was successfully prepared by hydrothermal method. The properties and the photocatalytic activity of the prepared samples for hydrogen production under visible light irradiation were compared to those prepared by co-precipitation method. The Cu-doped Cd0.1Zn0.9S samples prepared by hydrothermal method showed both improved crystallinity and photoabsorption ability as compared to the undoped sample. On the other hand, even though Cu-doped Cd0.1Zn0.9S prepared by co-precipitation method also showed improved photoabsorption ability in the visible light region, the samples showed poor crystallinity compared to the undoped one. With the same amount of Cu dopant, all samples prepared by hydrothermal method were found to exhibit higher photocatalytic activity for hydrogen production than the samples prepared by co-precipitation method. It was revealed that the amount of Cu dopant, crystallinity and narrow band gap energy are important factors to obtain highly active and stable photocatalysts.